Digital microfluidics and nuclear magnetic resonance spectroscopy for in situ diffusion measurements and reaction monitoring. Issue 4 (16th January 2019) - Swyer, Ian; von der Ecken, Sebastian; Wu, Bing; Jenne, Amy; Soong, Ronald; Vincent, Franck; Schmidig, Daniel; Frei, Thomas; Busse, Falko; Stronks, Henry J.; Simpson, André J.; Wheeler, Aaron R.
Abstract : We describe a two-plate digital microfluidic method for interfacing with nuclear magnetic resonance spectroscopy (DMF-NMR) for microscale chemical analysis. Abstract : In recent years microcoils and related structures have been developed to increase the mass sensitivity of nuclear magnetic resonance spectroscopy, allowing this extremely powerful analytical technique to be extended to small sample volumes (<5 μl). In general, microchannels have been used to deliver the samples of interest to these microcoils; however, these systems tend to have large dead volumes and require more complex fluidic connections. Here, we introduce a two-plate digital microfluidic (DMF) strategy to interface small-volume samples with NMR microcoils. In this system, a planar microcoil is surrounded by a copper plane that serves as the counter-electrode for the digital microfluidic device, allowing for precise control of droplet position and shape. This feature allows for the user-determination of the orientation of droplets relative to the main axes of the shim stack, permitting improved shimming and a more homogeneous magnetic field inside the droplet below the microcoil, which leads to improved spectral lineshape. This, along with high-fidelity droplet actuation, allows for rapid shimming strategies (developed over decades for vertically oriented NMR tubes) to be employed, permitting the determination of reaction-product diffusion coefficients as well as quantitative monitoring of reactive intermediates. We propose that this system paves the way for new and exciting applications for in situ analysis of small samples by NMR spectroscopy.